Assessment of inbreeding resulting from selection for scrapie resistance: a model for rare sheep breeds - Brown, Catherine J.; Orford, Michael R.; Mavrogenis, Andreas; Tzamaloukas, Ouranios; Miltiadou, Despoina (My University, 2014)
nbreeding in a small population of Chios sheep undergoing intense selection for the PrP gene was assessed 10 years after the beginning of a scrapie resistance selection programme. Inbreeding in this stock, already under selection for production traits, was analysed by using pedigree records containing 10,492 animals from 1968 to 2008, and also by genotyping 192 individuals with a panel of 15 microsatellites. Genetic markers indicated a loss of heterozygosity (FIS over all loci was 0.059) and allelic diversity (mean effective number of alleles was 3.075±0.275). The annual rate of inbreeding increased significantly after the start of the scrapie resistance programme, ΔF=0.005 compared with ΔF=0.001 before 1999, and was subjected to several genetic bottlenecks, mainly due to the low initial frequency of resistant animals. However, the mean individual inbreeding coefficient estimated from the pedigree - in this closed stock resembling the case of a rare breed - stood at the level of 4.5 per cent, five generations after the implementation of selection for the PrP gene. The inbreeding coefficient estimated by genetic markers was 4.37 per cent, implying that such a marker panel could be a useful and cost-effective tool for estimating inbreeding in unrecorded populations.
Keywords: Genetic Diversity; Inbreeding; Rare Breed; Scrapie Resistance; Sheep; Animalia; Ovis aries